Conservation of Chitin-Induced MAPK Signaling Pathways in Rice and Arabidopsis - Yamada, Kenta; Yamaguchi, Koji; Yoshimura, Satomi; Terauchi, Akira; Kawasaki, Tsutomu (Plant and cell physiology, 2017)
Perception of microbe-associated molecular patterns (MAMPs) including chitin by pattern recognition receptors (PRRs) rapidly induces activation of mitogen-activated protein kinase (MAPK) cascades. However, how PRRs transmit immune signals to the MAPK cascade is largely unknown. Recently, Arabidopsis receptor-like cytoplasmic kinase PBL27 has been reported to activate MAPKs through phosphorylation of AtMAPKKK5 in the chitin signaling pathway. In this study, we found that OsRLCK185, a rice ortholog of PBL27, regulates chitin-induced MAPK activation in a similar fashion to PBL27 in rice. Upon chitin perception, OsRLCK185 is phosphorylated by OsCERK1, a component of the chitin receptor complex. OsRLCK185 interacted with OsMAPKKK11 and OsMAPKKK18, rice orthologs of AtMAPKKK5, in yeast two-hybrid assays. Silencing of both OsMAPKKK11 and OsMAPKKK18 significantly reduced chitin-induced activation of OsMPK3 and OsMPK6. Expression levels of OsMAPKKK18 were much higher than that of OsMAPKKK11 in rice cells, which was consistent with the fact that the Osmapkkk11 single mutation did not affect MAPK activation. This result suggested that OsMAPKKK18 plays a more important role than OsMAPKKK11 in the chitin-induced activation of OsMPK3 and OsMPK6. The bimolecular fluorescence complementation (BiFC) experiment indicated that OsRLCK185 interacted with OsMAPKKK18 at the plasma membrane in planta. In vitro phosphorylation experiments showed that OsRLCK185 directly phosphorylates OsMAPKKK18. Furthermore, OsMAPKKK18 interacted with the MAPKK OsMKK4, the upstream component of OsMPK3/6. These results suggested that OsRLCK185 connects the chitin receptor to the MAPK cascade consisting of OsMAPKKK18-OsMKK4-OsMPK3/6. Our data revealed that chitin-induced MAPK activation in rice and Arabidopsis is regulated by common homologous elements.